Economic Growth: Export, Import, Crude Oil Prices, Exchange Rate - Vidalia, Dilla; Hariyani, Diyah Santi; Sulistiyowati, Liliek Nur (Universitas PGRI Madiun, 2024)
The Russia - Ukraine war has had an impact on the global economy and Indonesia is no exception. This study aims to determine the effect of exports, imports, crude oil prices and the rupiah exchange rate on economic growth in Indonesia. This study uses quantitative methods and sampling using saturated sampling techniques with secondary data samples from the official website of Statistics Indonesia (https://www.bps.go.id/), Bank Indonesia (https://www.bi.go.id/) and Investing.com (https://id.inveisting.com/) for the quarterly period 2008 - 2022 as many as 60 samples with the help of SPSS software version 29. The results showed that exports had a significant positive effect on economic growth. Imports have a significant positive effect on economic growth. Crude oil prices have a significant negative effect on economic growth. The rupiah exchange rate has a significant positive effect on economic growth. This indicates that when exports, imports, crude oil prices, and exchange rates decrease or increase, it will affect Indonesia's economic growth.